Research of possibilities of usage orthogonal package wavelet multiplexing in radioaccess MIMO systems - Марчук, А.В. (Eastern-European Journal of Enterprise Technologies, 2010)
Possibilities of the use of different wavelet bases are investigational for the construction of the of radioaccess MIMO systems with ortogonal package wavelet multiplexing and the adaptive method of dejaming is offered on the basis of choice of optimal structure of wavelet trees.